Natural and anthropogenic enrichments of molybdenum, thorium, and uranium in a complete peat bog profile, Jura Mountains, Switzerland - Krachler, Michael; Shotyk, William (Journal of environmental monitoring, 2004)
A core from an ombrotrophic Swiss bog representing 12 370 14C years of peat accumulation was evaluated as a possible archive of atmospheric deposition of Mo, Th and U. Calcium, Sr, and Ba were also determined to quantify weathering inputs, Mn to follow possible redox transformations, and Rb to identify plant uptake. Each of these elements was determined using ICP-MS, following digestion in a microwave heated autoclave using 3 ml HNO3 and 0.1 ml HBF4. Calcium and Sr clearly identify the thickness of the ombrotrophic zone because they are enriched in the minerogenic zone relative to the concentration of mineral matter. The concentration of Ba, however, is proportional to the concentration of mineral matter in all samples, and is not added to peat column by weathering reactions at the peat-sediment interface. The lowest element concentrations are found during the Holocene climate optimum (5320 to 8030 14C year BP) with the following natural background values (n = 18): Mo 0.08 ± 0.02 µg g−1, U 0.029 ± 0.008 µg g−1, Ba 5.2 ± 2.6 µg g−1, Th 0.070 ± 0.022 µg g−1 and Rb 0.63 ± 0.09 µg g−1. By far the highest concentrations of Ba, Mn, Rb and Th were found during the Younger Dryas cold climate event (10 590 14C year BP) when the flux of atmospheric soil dust was at its post-glacial maximum. Molybdenum and U are elevated in concentration throughout the minerogenic zone because of sediment weathering and this masks the atmospheric signal in samples older than ca. 8000 14C year BP (ca. 9000 calendar years). Enrichment factors (EF) calculated using Sc as a conservative, lithogenic element shows that minerogenic peats are enriched in Mo up to 18× and U 26×, relative to the natural “background” values. During the two millennia prior to industrialisation, the accumulation rate of atmospheric Mo averaged 0.23 ± 0.13 µg m−2 year−1. With the onset of the Industrial Revolution, Mo accumulation rates rapidly and continuously increased to approximately 10 µg m−2 year−1 in the late 1980s. These data suggest that Mo in atmospheric aerosols today is derived predominately from anthropogenic emissions. Uranium does not show the same enrichment pattern which suggests that steel-making rather than coal combustion is the primary source of atmospheric Mo contamination at this site.